2012
DOI: 10.3354/cr01079
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the sensitivity of outdoor recreation activities to climate change

Abstract: This study develops a methodological framework to analyze the climate sensitivity as well as climate change impacts on outdoor recreation activities, applied to a case study of 2 lidos in the city of Zurich. A negative binomial regression is used to link daily data on lido entries with weather variables for the period 2003 to 2010, while controlling for non-climatic factors (such as weekends and school holidays). It shows that the number of lido visitors is significantly determined by weather conditions such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Some studies have analysed the relationship of temperature and weather on the allocation of leisure time and outdoor recreation (Zivin and Neidell 2014;Finger and Lehmann 2012). In addition to the impact of climatology, individuals are usually on holiday during the summer, and this may encourage leisure activities.…”
Section: Zinb Count Data Estimates: Education Versus Earningsmentioning
confidence: 99%
“…Some studies have analysed the relationship of temperature and weather on the allocation of leisure time and outdoor recreation (Zivin and Neidell 2014;Finger and Lehmann 2012). In addition to the impact of climatology, individuals are usually on holiday during the summer, and this may encourage leisure activities.…”
Section: Zinb Count Data Estimates: Education Versus Earningsmentioning
confidence: 99%
“…Weekly effort estimates are available starting in 2015 (with weeks defined as starting on Monday and ending on the following Sunday) and are available spatially across five inshore coastal study areas shown in Fig 1a: Pontchartrain (1), Barataria (3), Terrebonne/Timbalier (5), Vermilion/Teche (6), and Calcasieu (7) as well as a single aggregated offshore area. Effort within coastal study areas is further split into charter or private, and for this analysis we only consider private data, which represents individual recreational anglers.…”
Section: Data Preparationmentioning
confidence: 99%
“…Other studies have focused on specific weather variables. Paudyal et al [6] reported the greatest number of daily visitors to the Florida National Scenic Trail to occur between 16-22˚C (among other findings), and Finger and Lehmann [7] documented temperature and rainfall to be significant factors in driving visitors to lidos (public beaches) in Switzerland. On a seasonal level, disparities in weather patterns between the mid-latitudes and tropical regions are a huge driver of the Caribbean tourism season [8].…”
Section: Introductionmentioning
confidence: 96%
“…However, over the last decades, there has been an increasing interest on determining whether meteorological conditions at the destination place affect tourism demand. Apart from those articles addressing the “sun, sea, and sand” type of tourism, most studies have found weather conditions as a significant variable affecting tourism demand as well as attendance to outdoor activities (Agnew and Palutikof, 2006; Aylen et al, 2014; Finger and Lehmann, 2012; Goh, 2012; Otero-Giráldez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%